1977
DOI: 10.1007/bf02533346
|View full text |Cite
|
Sign up to set email alerts
|

Glycerokinase in human adipose tissue

Abstract: The presence of glycerokinase has been demonstrated in human omental and subcutaneous adipose tissue. The enzyme reaction showed a linear time course for 5 min at 30 C and pH optima at pH 7.6 and 9.0. Saturation of the enzyme was observed at 1.8 mM adenosine triphosphate (ATP) and the double reciprocal plot of activity vs. ATP concentration was nonlinear giving two apparent Km values of 0.094 and 0.518 mM. The apparent Km for glycerol, 0.112 mM, was obtained from a linear double reciprocal plot, and the enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…GyK catalyzes direct conversion of glycerol to glycerol-3-phosphate. By comparison with BAT, GyK activity in human WAT is low (28). In human white fat cells, we showed that PGC-1␣ strongly induces GyK gene expression and activity.…”
Section: Discussionmentioning
confidence: 77%
“…GyK catalyzes direct conversion of glycerol to glycerol-3-phosphate. By comparison with BAT, GyK activity in human WAT is low (28). In human white fat cells, we showed that PGC-1␣ strongly induces GyK gene expression and activity.…”
Section: Discussionmentioning
confidence: 77%
“…8 However, it was also considered that TAG accumulation in adipocytes was predominantly attributed to the elevated activity of G3PDH owing to the low activity of glycerokinase, fatty acid synthase and adenosine triphosphate-citrate lyase. 45,46 Currently, G3PDH activity significantly decreased both in psiRNA-AGT1-and psiRNA-AGT2-transfected cells compared with the negative control group (Figure 2). Moreover, G3PDH activity decreased by 22% (psiRNA-AGT1 vs psiRNA-AGT0 (day 6):147.93 ± 9.64 vs 189.74 ± 10.72) or less.…”
Section: Agt Knockdown Inhibits Hpa-v Differentiation Z-w Ye Et Almentioning
confidence: 93%
“…Both direct and indirect glycerol incorporation rates are provided (see "Materials and Methods" for calculation). Glucose incorporation was measured in additional studies using [6][7][8][9][10][11][12][13][14] C]glucose alone (fed) or together with H]glucose (fasted). Statistical comparisons of incorporation rates of glycerol (direct incorporation only) and glucose ( [6-14 C]glucose-measured rates only) is on a carbon-equivalent basis (glucose incorporation rate ϫ 2).…”
Section: Discussionmentioning
confidence: 99%
“…Glycerol can be converted directly to G3P by glycerol kinase, but this is believed to occur primarily, if not solely, in the liver and kidney because the glycerol kinase activity in these tissues is sufficient to permit large quantities of blood glycerol to be used for gluconeogenesis and TG synthesis. The direct conversion of free glycerol to G3P is thought to be negligible in skeletal muscle and adipose tissue because of their low activities of glycerol kinase (5)(6)(7)(8). A corollary to this supposition is that glycerol generated by the hydrolysis of TG in skeletal muscle quantitatively enters the circulation.…”
mentioning
confidence: 99%